2019
DOI: 10.4102/sajim.v21i1.1108
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of use of electronic information resources by the professoriate in Nigerian universities: Extending the unified theory of acceptance and utilisation of technology model

Abstract: Background: This study examined the determinants of use of electronic resources by the professoriate in the social sciences and humanities departments of three universities in Nigeria. The constructs of the unified theory of acceptance and utilisation of technology (UTAUT), namely, performance expectancy, effort expectancy, social influence and facilitating conditions, were used as determinants, and were extended to include self-efficacy, attitude and anxiety because of their theoretical and practical signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, the extent to which faculty believe that using the resources would improve their research prospects (performance expectancy) varies significantly. For example, 77% of respondents who are in the professorate cadre submitted in a study that they constantly obtain teaching and research information from e-learnings database (Nwone and Mutula 2019 ). For these individuals, the frequency with which they obtain information from the e-learning databases will reveal their PE level of the technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, the extent to which faculty believe that using the resources would improve their research prospects (performance expectancy) varies significantly. For example, 77% of respondents who are in the professorate cadre submitted in a study that they constantly obtain teaching and research information from e-learnings database (Nwone and Mutula 2019 ). For these individuals, the frequency with which they obtain information from the e-learning databases will reveal their PE level of the technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Taken together, these studies show that these three characteristics can have an important impact on computer use and the ability to learn to use electronic resources efficiently. Computer self-efficacy has been positively related to performance during computer training (Nwone and Mutula, 2019; Oyewole and Oladepo, 2017; Sultan and Kanwal, 2017).…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Taken together, these studies show that these three characteristics can have an important impact on computer use and the ability to learn to use electronic resources efficiently. Computer self-efficacy has been positively related to performance during computer training (Nwone and Mutula, 2019;Oyewole and Oladepo, 2017;Sultan and Kanwal, 2017). Tolulope (2017) similarly reported that personal factors (gender, age, level of study), computer self-efficacy, and computer anxiety significantly determined the use of electronic library resources by university students in New Zealand.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…It is worth noting that the last two studies (Osih andSigh, 2020 andTao, 2008) made similar findings because both studies were underpinned by the TAM. The point of difference from the first study (Nwone and Mutula, 2019) is the use of the extended UTAUT model, which explains the difference in the determinants of use.…”
Section: Determinants Of Use Of Electronic Resourcesmentioning
confidence: 94%
“…Studies have been conducted to gain insight into the factors that have direct and indirect impacts on students' use of electronic information resources for academic purposes. Nwone and Mutula (2019) investigated the determinants of the use of electronic information resources by social science and humanities professors in three federal universities in Nigeria. The study adopted a descriptive survey where a questionnaire was used to collect the data.…”
Section: Determinants Of Use Of Electronic Resourcesmentioning
confidence: 99%